السياسات التعليمية في الفكر الإسلامي مدخل لتعزيز البناء الاجتماعي - Hamid Hadi Baden ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Educational policies are among the new concepts in the strategic planning of the state in general and education in particular, and the demands addressed in this research establish an Islamic methodology and intellectual vision stemming from the basic goal of the teaching and learning process, which is community service. The researcher discussed the Qur’anic foundations of educational policies and the rooting of this concept in the Islamic heritage, based on the hadiths and biography of the Noble Prophet Muhammad, peace and blessings of God be upon him and his family, as well as the biography of the righteous predecessors As well as in the context of rooting the social structure in Islamic thought, which considers the educational institution to be the second institution after the family, which raises the structure of society, we transform advancement, prosperity and progress by providing society with the outcomes of the educational process from specialized and qualified human resources to sustain the momentum of development. Finally, the discussion comes in the context of adopting theories of promoting social responsibility, which educational policies contribute directly to through the vision they provide for the future